1997
DOI: 10.1046/j.1365-232x.1997.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to entry into the PFI market

Abstract: This paper reports early results of a study of construction contractors and their experiences of the PFI market. Utilizing material from semi‐structured interviews with three categories of construction contractor, small, medium and large, consideration is given to the barriers to entry which contractors face when approaching the PFI market. The paper highlights six barriers of entry: lack of appropriate skills; high participation costs; high project values; high risk; lack of credibility and contacts; and dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…These full‐service firms have the size, experience in general project management, reputation, and financial capacity to take a lead role in multiple public‐private partnership bids and to obtain external investments (Ezulike, Perry, and Hawwash 1997). Put differently, full‐service firms in each sector have experience working in contexts of complex project ecologies that require the coordination of numerous subcontractors and reciprocally related tasks.…”
Section: Stable Network: Public‐ and Private‐sector Partnersmentioning
confidence: 99%
“…These full‐service firms have the size, experience in general project management, reputation, and financial capacity to take a lead role in multiple public‐private partnership bids and to obtain external investments (Ezulike, Perry, and Hawwash 1997). Put differently, full‐service firms in each sector have experience working in contexts of complex project ecologies that require the coordination of numerous subcontractors and reciprocally related tasks.…”
Section: Stable Network: Public‐ and Private‐sector Partnersmentioning
confidence: 99%
“…At the microscope level, the high risk nature of PPPs constitutes a barrier to entry for market participants (Ezulike et al, 1997). For those who are able to afford competing in this highly risky business, risk assessments were chiefly based on past experience and intuition with little attention given to political and reputational risks (Asenova and Beck, 2003;Johnston and Gudergan, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In this paper the approach taken uses the distinction between homogeneous and differentiated products based on the ability of contractors to specialise in specific markets or types of projects (see de Valence 2003). Ezulike et al (1997) also found that significant barriers to entry existed for Private Finance Initiative (PFI) projects in Scotland and some large contractors were specialising in these projects.…”
Section: Product Homogeneitymentioning
confidence: 99%
“…Although barriers to entry are clearly important there has to date been limited consideration of their role in the construction industry. Previous research by Ezulike et al (1997), , and de Valence (2003) showed that barriers do exist, and established that they play a role in the industry.…”
Section: Introductionmentioning
confidence: 95%